The Macroeconomic Impact of Changes in Income Taxes in the Short and Medium Runs - Hall, Robert E. (Journal of Political Economy, 1978)
The effects of an unexpected change in income taxes are studied in a model with full rational expectations. In the short run, aggregate supply is quite price elastic because commitments to pay predetermined wages are made 1 or more years in advance. The model also recognizes the limited response of investment to unexpected developments in the short run. The paper finds that much of the effect of unexpected tax policy operates through inflationary expectations–an economy with rational expectations is more responsive to tax changes than is one with naive expectations.